Emerging role of Hippo signalling pathway in bladder cancer. Issue 1 (7th August 2017) - Xia, Jianling; Zeng, Ming; Zhu, Hua; Chen, Xiangjian; Weng, Zhiliang; Li, Shi
Abstract: Bladder cancer (BC) is one of the most common cancers worldwide with a high progression rate and poor prognosis. The Hippo signalling pathway is a conserved pathway that plays a crucial role in cellular proliferation, differentiation and apoptosis. Furthermore, dysregulation and/or malfunction of the Hippo pathway is common in various human tumours, including BC. In this review, an overview of the Hippo pathway in BC and other cancers is presented. We focus on recent data regarding the Hippo pathway, its network and the regulation of the downstream co‐effectors YAP1/TAZ. The core components of the Hippo pathway, which induce BC stemness acquisition, metastasis and chemoresistance, will be emphasized. Additional research on the Hippo pathway will advance our understanding of the mechanism of BC as well as the development and progression of other cancers and may be exploited therapeutically.